Mappings on C*-algebras preserving the sum of absolute values. Issue 2 (1st February 2018) - Taghavi, Ali; Hosseinzadeh, Roja
Abstract : Let and be two unital -algebras. We consider the surjective maps which satisfy for every, where is a -algebra of real rank zero. We show that all these maps are linear or antilinear -homomorphism multiplied by a central element.